Maternal and neonatal outcomes of childbirth care in a Freestanding Birth Centre - Nathalie Leister; Gisele Almeida Lopes; Caroline de Oliveira Ferreira Iguchi; Thalita Vital Botelho; Maria Luiza Gonzalez Riesco (Revista Latino-Americana de Enfermagem)
Objective: to compare maternal and neonatal care outcomes based on women’s parity and to describe neonatal morbidity and mortality among newborns of women admitted in labor. Method: a cross-sectional study involving 3,397 women admitted for childbirth at a Freestanding Birth Centre and their newborns. The exposure variable was parity, and the outcomes included the use of oxytocin and amniotomy, type of birth, perineal trauma, postpartum hemorrhage, maternal and neonatal transfer, and newborn admission to neonatal intensive or intermediate care units. Data were analyzed descriptively and through logistic regression. Results: primiparity was associated with a higher likelihood of receiving oxytocin and amniotomy, intrapartum transfer, second-degree tear, episiotomy, postpartum hemorrhage, cesarean section, forceps-assisted birth, and neonatal admission to neonatal intensive or intermediate care units. Births predominantly occurred in semi-seated and upright positions, either on a bed or in the birthing tub. The maternal transfer rate was 21.8%, while the neonatal transfer rate was 3.3%. Conclusion: primiparity is a predictor of the analyzed interventions and unfavorable maternal and neonatal outcomes. However, the studied Freestanding Birth Centre can be considered a safe setting for childbirth among health pregnant women.